EKRANISASI NOVEL ANKOKU JOSHI KARYA AKIYOSHI RIKAKO KE LIVE ACTION - Hanifa Muslima; Fenny Febrianty; Pitri Haryanti (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2021)
The purpose of this study is to identify the impact of the reduction of Sonoko Koga's character in the ecranization from novel Ankoku Joshi by Akiyoshi Rikako to live action Ankoku Joshi by director Saiji Yakumo. The research method used is descriptive analysis method. The results of this study indicate the impact of reducing Sonoko Koga's character in the ecranization on other figures. The conclusions obtained from this study is the shringkage or reduction of Sonoko Koga's character in ecranization has an impact on the characterization of the characters Takaoka Shiyo and Nitani Mirei in order to complement the role of Sonoko Koga in the story of Ankoku Joshi. The aspirations of the Sonoko Koga character are not varied from other characters because they are considered to have no effect on the content of the live action story of Ankoku Joshi.